(untitled) (Research, Society and Development, 2022)
Introduction: Keratocyst is a benign tumor that affects mostly adult male patients under 40 years old. It is equivalent to 12% of all odontogenic cysts in the maxillofacial region. Clinically, larger lesions may present pain, swelling and drainage, and their diagnosis is confirmed by imaging together with histopathology. Objective: The present study aims to report a case of Odontogenic Keratocyst, associated with an impacted tooth 18 that invades the right maxillary sinus, in a 22-year-old male feoderm patient. Discussion: The study has great relevance due to its rarity of involvement in the maxillary sinus, since its involvement occurs in less than 1% of cases. The treatment includes some surgical options or combined therapies, with no unanimity among the authors, but it deserves special consideration due to its specific clinical behavior. Conclusion: The treatment plan recommended a surgical intervention, aiming at the maintenance of the noble structures, in order to improve the prognosis and reduce the risk of recurrence of the lesion. It is necessary to follow up the patient with periodic long-term evaluations.